Evaluating the Effectiveness of Investment in Environmental Projects for the Synergistic Effect (Economic journal of Lesya Ukrainka Volyn National University, 2015)
The author singled types of investments in environmental projects; analysis methodologies to assess feasibility of investment. Determined additional effects on investment in environmental projects in areas of the company. It assesses the feasibility of water system improvements drinking water synergistic effect.
Keywords: environmental investment, effect of synergies, efficiency